Invisible symmetries: Superheroes, Grant Morrison and Isaiah Berlin's two concepts of liberty. Issue 2 (1st October 2013) - Murray, Chris
Throughout his career in comics Scottish writer Grant Morrison has interrogated concepts of liberty and power and their relationship to revolutionary action, often using the superhero as a metaphor. This article examines liberalism in his work with reference to the ideas of political philosopher Isaiah Berlin (1909–1997), whose influential lecture 'Two Concepts of Liberty' ([1958] 2002), described the dangers of 'positive liberty', and set out the case for the virtues of 'negative liberty'. Both Berlin and Morrison were profoundly influenced by the Cold War, and the philosophical and ideological arguments about the definition of freedom that arose from it. The superhero was also shaped by these debates, and Morrison's liberalism, as expressed through his writing in this genre, owes much to the distinctions Berlin put in place. This article argues that a greater understanding of the politics of the superhero, and Morrison's changing attitude towards the genre and its underlying themes of identity and freedom, can be gained by applying Berlin's schema. Indeed, several of Morrison's key works, such as Zenith (1987–1993), The Invisibles (1994–2000), Flex Mentallo (1996) and All Star Superman (2005–2008), dramatize the struggle between positive and negative concepts of liberty, but his views have undergone shifts, from a rather sceptical conception of the superhero in his early work to the point where he now enshrines the superhero as the best example of liberty and aspiration.